2014
DOI: 10.1186/1471-2164-15-1038
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA gene families in the genomes of anopheline mosquitoes

Abstract: BackgroundOnly a small fraction of the mosquito species of the genus Anopheles are able to transmit malaria, one of the biggest killer diseases of poverty, which is mostly prevalent in the tropics. This diversity has genetic, yet unknown, causes. In a further attempt to contribute to the elucidation of these variances, the international “Anopheles Genomes Cluster Consortium” project (a.k.a. “16 Anopheles genomes project”) was established, aiming at a comprehensive genomic analysis of several anopheline species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…More than one hundred transcripts were targeted by two or more miRNAs. Meanwhile, 50 transcripts were regulated by miRNAs in different regions, suggesting that miRNAs are involved in complicated regulatory networks as suggested by other studies [ 8 , 36 , 50 ]. The conserved miRNAs in An.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…More than one hundred transcripts were targeted by two or more miRNAs. Meanwhile, 50 transcripts were regulated by miRNAs in different regions, suggesting that miRNAs are involved in complicated regulatory networks as suggested by other studies [ 8 , 36 , 50 ]. The conserved miRNAs in An.…”
Section: Discussionmentioning
confidence: 57%
“…Compared with miRNA genes predicted from the genome of An. sinensis by Dritsou et al [ 36 ] (Additional file 4 : Table S4), 19 miRNAs (asi-miR-252, asi-miR-10, asi-miR-927, asi-miR-8, asi-miR-996, asi-miR-1, asi-miR-276, asi-miR-305, asi-miR-277, asi-let-7, asi-miR-283, asi-miR-210, asi-miR-133, asi-miR-988, asi-miR-275, asi-miR-315, asi-miR-14, asi-miR-31 and asi-miR-999) in the An. sinensis were shared within three databases as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, 22 contigs in the assembly were found to contain rDNA sequences, a family of genes that is known to be extremely difficult to be assembled correctly in WGS (Whole Genome Sequence) projects. 60 The most abundant elements of the 'Other' class of Table 4 includes (but is not limited to) the fruit fly elements 17.6, S, Doc, Bari1, piwi, F, TART and Asterix as well as the rice gypsy-type retrotransposon; these are listed in decreasing order of frequency identified, which, in no case, was higher that 0.2%. A recent publication reported the assembly of the 'repeatome' of A. albopictus.…”
Section: Annotationmentioning
confidence: 99%
“…The major drawback of the homology‐based analysis is that by definition, it detects only broadly conserved miRNA genes. This limitation was partially overcome by a conservative ab initio prediction coupled with homology searches of 16 Anopheles genomes . This study validated 58 previously identified miRNAs, discovered five new genes and revealed 21 miRNAs common to all species within the Anopheles complex.…”
Section: Mirna Expression In a Gambiaementioning
confidence: 55%
“…Studies in late larval stages confirmed high levels of expression of these miRNA and revealed stage‐specific enrichment of miR‐11, miR‐276 and miR‐306 . Conservation of miR‐8 and miR‐10 in all Anopheles species indicates a conserved role of these abundantly expressed miRNAs in mosquito biology . Interestingly, sequences of the 20 most abundant miRNAs make up for 96% of all RNAseq reads, highlighting a dramatic difference in expression levels of miRNAs .…”
Section: Mirna Expression In a Gambiaementioning
confidence: 87%